The Description of Coping Strategies in Working Mothers: Description of Coping Strategies in Working Mothers - Muhammad Rizal Fikri; Ira Darmawanti (Universitas Negeri Surabaya, 2023)
This study aims to look at the description of coping strategies in working mothers and what pressures and conflicts are faced by working mothers. This study uses a qualitative case study approach. Data collection in this study was semi-structured interviews with two subjects who are working mothers who have children aged 0-18 years. Data analysis in this study uses analytical techniques from Miles and Huberman, the process of which is through data collection, data reduction, data presentation, and drawing conclusions. The results of this study were that the second subject used two types of coping strategies, namely coping that focuses on problems (problem focused coping), namely seeking social support and planful problem solving. whereas for emotion-focused coping, namely distance and positive reappraisal. While the pressures and conflicts faced by working mothers are pressure and conflict at work and also managing the household. There are also difficulties in dividing time for working mothers between work matters and household responsibilities.